Pulse transit time in pregnancy: a new way to diagnose and classify sleep disordered breathing?. Issue 5 (8th February 2019) - Link, Brittany N; Eid, Celine; Bublitz, Maggie H; Pengo, Martino F; Salameh, Myriam; Ludwig, Karin S; Millman, Richard P; Dworkin, Lance; Bourjeily, Ghada
Abstract: Study Objectives: There are significant discrepancies between the prevalence of snoring and that of objectively defined sleep disordered breathing among pregnant women, suggesting subtle airflow limitations that may not be captured by conventional scoring. This study examined the performance of pulse transit time, an indirect measure of arterial stiffness and sympathetic activation, in pregnancy. Methods: Pregnant women with obesity and snoring and a group of controls without symptoms of sleep disordered breathing were recruited in the first trimester. Women underwent a level III in-laboratory sleep monitoring study including an electrocardiogram and pulse oximetry, and pulse transit time was measured. Sleep disordered breathing was defined as an apnea–hypopnea index at least five events per hour of sleep. Statistical analysis was performed using Spearman correlation, Fisher's exact t -test, and univariate analysis. Results: Of the 222 women, 38 met criteria for sleep disordered breathing. Pulse transit time drops were very prevalent (95% of participants with snoring had > 5 drops per hour). Median apnea–hypopnea index was 0.7 (interquartile range [IQR]: 2.6) events per hour whereas median pulse transit time drop index was 20.70 (IQR: 35.90) events per hour. Pulse transit time index was significantly higher in snorers with apnea–hypopnea index less than five events per hours and participants with apnea–hypopnea index greater than five events per hour compared to controls. Examination of random epochs with pulse transit time drops showed that 95% of pulse transit time drops were associated with airflow limitation. Conclusions: Pulse transit time ascertains frequent events of sympathetic activation in at-risk women with and without sleep disordered breathing beyond conventional apneas and hypopneas. Pulse transit time may be an important addition to the identification of clinically significant sleep disordered breathing in pregnant women, and may identify more sleep disordered breathing than apnea–hypopnea index.